Interactional Model of Digital Managerial Competence of Kindergarten Teachers in North Sulawesi - Rawung, Refien Khouni Silva; Lumapow, Harol R.; Palilingan, Verry Ronny; Lengkong , Jeffry Sony Junus (International Journal of Information Technology and Education, 2023)
This study aims to analyze and explain the interactional model of digital managerial competence of kindergarten teachers in North Sulawesi Province. This research was conducted using a survey method, a sample of 96 kindergarten teachers in North Sulawesi Province, questionnaire data collection techniques, and correlation data analysis techniques. The results of the study show that there is a positive and significant independent and simultaneous relationship between digital leadership, teleworking, internet skills, teacher-parent digital communication, and motivation with digital managerial competencies of kindergarten teachers. In addition, the results of the research are discussed and conclusions and suggestions are presented.